Antimicrobial peptides/ciprofloxacin-loaded O-carboxymethyl chitosan/self-assembling peptides hydrogel dressing with sustained-release effect for enhanced anti-bacterial infection and wound healing. (15th March 2022) - Huan, Yuchen; Kong, Qing; Tang, Qingjuan; Wang, Yuming; Mou, Haijin; Ying, Rui; Li, Chunjun
Abstract: Bacteria-induced wound infections and multifunctional hydrogels have received widespread attention in wound repair. In this study, self-assembling peptides (SAPs) were grafted on O -carboxymethyl chitosan (O-CMCS), and compact spatial structure and good drug sustained-release effect on mel-d1, a new AMP designed based on melittin with the same antimicrobial activity but lower cytotoxicity and ciprofloxacin (CIP) were obtained. In vivo test showed that the O-CMCS/SAP hydrogel loaded with CIP and mel-d1 accelerated the wound closure speed caused by infection of Escherichia coli and skin tissue regeneration. Both of the enhanced interaction between O-CMCS/SAP and CIP/Mel-d1 because of the hydrophobic interaction and π-π stacking, and the potential tissue healing ability of SAP played important roles. This study provided a rational design method of O-CMCS by grafting SAPs to give a wider range of biological functions. Graphical abstract: a) Design of the new antimicrobial peptide, b) conjugation of O-CMCS and SAP by EDC/NHS, c) the microstructure, molecular forces and wound repair process of the hydrogel. Unlabelled Image